4 SPECIES OF BRAZILIAN POISON FROGS RELATED TO EPIPEDOBATES-PICTUS (DENDROBATIDAE) - TAXONOMY AND NATURAL-HISTORY OBSERVATIONS - Haddad, CFB; Martins, M. (Herpetologists League, 1994)
We present morphological and natural history data on Epipedobates pictus and three additional taxa currently regarded as synonyms of the former: Epipedobates braccatus, E. flavopictus, and E. hahneli. Topotypes of the four species were examined. Morphological data on tadpoles and adults, in addition to distribution patterns and vocalizations, indicate that the four taxa represent distinct species. Two groups are evident within them: (1) the slender-bodied, Amazonian E. hahneli with small flash marks on the thighs and a low-finned tadpole, and (2) the robust bodied, almost extra-Amazonian E. braccatus, E. flavopictus, and E. pictus with large flash marks on the thighs and tadpoles with fins of moderate height.
Keywords: TAXONOMY; AMPHIBIA; DENDROBATIDAE; EPIPEDOBATES; VOCALIZATIONS; DISTRIBUTION; TADPOLES; NATURAL HISTORY